1974
DOI: 10.1029/ja079i028p04227
|View full text |Cite
|
Sign up to set email alerts
|

The Earth as a radio source: Terrestrial kilometric radiation

Abstract: Radio wave experiments on the Imp 6 and 8 satellites have shown that the earth emits very intense electromagnetic radiation in the frequency range of about 50–500 kHz. At peak intensity the total power emitted in this frequency range is about 109 W. The earth is therefore a very intense planetary radio source, with a total power output comparable to the decametric radio emission from Jupiter. We refer to this radio emission from the earth as terrestrial kilometric radiation. Terrestrial kilometric radiation ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

29
345
0
9

Year Published

1994
1994
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 538 publications
(386 citation statements)
references
References 14 publications
29
345
0
9
Order By: Relevance
“…A DC offset is present in the measurement due to lowfrequency electromagnetic field components associated with the electron beam propagation. After 180 ns, a peak rf output power of 3 kW was measured corresponding to an rf conversion efficiency of 1.1% -comparable with the estimate of 1% for the astrophysical phenomena (Gurnett 1974).…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…A DC offset is present in the measurement due to lowfrequency electromagnetic field components associated with the electron beam propagation. After 180 ns, a peak rf output power of 3 kW was measured corresponding to an rf conversion efficiency of 1.1% -comparable with the estimate of 1% for the astrophysical phenomena (Gurnett 1974).…”
Section: Resultssupporting
confidence: 78%
“…This trend is reflected in the results of unbounded PiC simulations of cyclotron-wave coupling, where radiation propagation has been observed with a distinctive backward-wave character to it, typically directed in a slightly backward direction, only a few degrees away from the perpendicular to the magnetostatic field. The corresponding rf conversion efficiencies are comparable with estimates for the astrophysical phenomena (Gurnett 1974;Treumann 2006;Bingham et al 2013). …”
Section: Discussionsupporting
confidence: 80%
“…The processes involved appear to be very similar to those occurring in Earth's magnetosphere. The comparable type of radio emission at Earth is auroral kilometric radiation, which is known to be closely associated with the terrestrial aurora 19 . Just as with the jovian hectometric radiation, the terrestrial kilometric radiation is highly variable and is closely correlated with magnetic storms 20 , including those triggered by interplanetary shocks.…”
mentioning
confidence: 99%
“…Early solar system exploration led to the discovery of hectometric radiation from Jupiter [Brown, 1974;Desch and Carr, 1974] and kilometric radiation from Saturn [Warwick et al, 1981], Uranus [Warwick et al, 1986], and Neptune [Warwick et al, 1989]. Auroral kilometric radiation (AKR) from the terrestrial polar region has been observed by Earth-orbiting satellites [Dunckel et al, 1970;Gurnett, 1974]. These planetary radio waves, whose emission frequency is very close to the local electron gyrofrequency, are generated by accelerated auroral electrons through the cyclotron maser instability [Wu and Lee, 1977;Pritchett, 1984;Pritchett and Strangeway, 1985].…”
Section: Introductionmentioning
confidence: 99%